Synthesis, antimicrobial and antioxidant activities of 1-(1,4-benzodioxane-2-carbonyl)piperazine derivatives - Mallesha, Lingappa; Mohana, Kikkeri Narasimhasetty (European Journal of Chemistry, 2011)
A series of novel 1-(1,4-benzodioxane-2-carbonyl)piperazine derivatives (6a-h) and (7a-e) were synthesized by nucleophilic substitution reaction of 1-(1,4-benzodioxane-2-carbonyl)piperazine (3) with various sulfonyl and acid chlorides. The newly synthesized compounds were characterized by elemental analyses, UV-visible, FT-IR, 1H NMR and LC-MS spectral studies. All compounds were evaluated for in vitro antibacterial, antifungal and antioxidant activities. Compound, 4-(2-trifluoromethyl)-benzenesulfonyl-1-(1,4-benzodioxane -2-carbonyl)piperazine (6b) exhibited significant antimicrobial activity against tested pathogenic bacterial and fungal strains. Compound, 4-(3-methoxy)-benzoyl-1-(1,4-benzodioxane-2-carbonyl)piperazine (7a) showed moderate antioxidant activity compared to standard drug by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay method.